1997
DOI: 10.1007/s11663-997-0073-8
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of solidification of metal-matrix particulate composites with convection

Abstract: A multiphase model for the alloy solidification of metal-matrix particulate composites with convection is developed. Macroscopic transport equations are written for each phase, with unknown parameters modeled through supplementary relations pertinent to the solidification of a binary alloy matrix containing a stationary solid phase and generally nonstationary spherical particles. The model is applied to various one-and two-dimensional systems containing an Al-7 wt pct Si/SiC composite. One-dimensional sediment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 63 publications
0
6
0
Order By: Relevance
“…The corresponding values for Al-7mass%Si alloy are almost the same as those adopted by Feller and Beckermann. 16) As shown in Table 1 Table 2. Heat transfer coefficient, h, corresponding to each value of T˙for different C 0 is obtained beforehand through several attempts.…”
Section: Simulation Proceduresmentioning
confidence: 99%
“…The corresponding values for Al-7mass%Si alloy are almost the same as those adopted by Feller and Beckermann. 16) As shown in Table 1 Table 2. Heat transfer coefficient, h, corresponding to each value of T˙for different C 0 is obtained beforehand through several attempts.…”
Section: Simulation Proceduresmentioning
confidence: 99%
“…(2012) observed that distribution of the reinforcement particles is dependent on the solidification rate, and at low solidification rates, the reinforcing particles are clustered. Before the occurrence of complete solidification of Al melt, Al will pass through a semisolid state called mushy state (Feller and Beckermann, 1997). Once the mushy state is reached, the reinforcement particles remain in their positions during solidification (Feller and Beckermann, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Before the occurrence of complete solidification of Al melt, Al will pass through a semisolid state called mushy state (Feller and Beckermann, 1997). Once the mushy state is reached, the reinforcement particles remain in their positions during solidification (Feller and Beckermann, 1997). Once inside the mush, macroscopic particle motion is largely prevented by the presence of microscopically complex solid–liquid interfaces called dendrites, which entrap the particles (Feller and Beckermann, 1997).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rohatgi et al 3) presented a simple one-dimensional model based on solidification experiment and studied the effect of stationary particle on temperature profiles and interface velocities. Beckermann et al 4,5) presented a multiphase model based on the volume-averaged technology and predicted the macroscopic particle distribution and the advancing speed of solidification front. Previous particle distribution simulation at microscopic scale mainly focused on the condition of unidirectional solidification and planar S/L interface, most of which studied the interaction process between sole or several particles and solidification interface.…”
Section: Introductionmentioning
confidence: 99%